The Outer Halos of Early-Type Galaxies. Issue Volume 10:Issue S311(2014) (10th April 2015) - Gerhard, Ortwin; Arnaboldi, Magda; Longobardi, Alessia
Abstract: The outer halos of massive early-type galaxies (ETGs) are dark matter dominated and may have formed by accretion of smaller systems during galaxy evolution. Here a brief report is given of some recent work on the kinematics, angular momentum, and mass distributions of simulated ETG halos, and of corresponding properties of observed halos measured with planetary nebulae (PNe) as tracers. In the outermost regions of the Virgo-central galaxy M87, the PN data show that the stellar halo and the co-spatial intracluster light are distinct kinematic components.